Advantages of incorporating Hygroscopic Cycle Technology to a 12.5-MW biomass power plant. (25th February 2018) - Rubio-Serrano, Francisco J.; Gutiérrez-Trashorras, Antonio J.; Soto-Pérez, Fernando; Álvarez-Álvarez, Eduardo; Blanco-Marigorta, Eduardo
Graphical abstract: Highlights: Hygroscopic Cycle Technology (HTC) improves Rankine cycle performance. HTC can increase by 13 °C the cooling temperature for a given pressure. Annual average electrical consumption of air coolers decreases from 320 to 112 kW. This technology saves 229, 200 m 3 /year of cooling water. HTC improves 2.5% the average electrical efficiency of the power plant. Abstract: This article focuses on the advantages found by incorporating Hygroscopic Cycle Technology into the 12.5-MWe "Vetejar" biomass power plant operating in the province of Córdoba (Spain) since 1996. The power plant required upgrades to increase its availability, net electrical performance and to extend the service life span of refrigeration equipment. The incorporation of the new Hygroscopic Cycle Technology has allowed not only to alleviate the shortcomings of the power station in a simple way, but also to make the most of the existing equipment, despite the adverse environmental conditions. The scarcity of water in the area is one of the greatest difficulties the plant has met since its start-up. It significantly diminishes the operation hours of the plant, reducing the electrical power generated, electrical performance and availability. The incorporation of this novel technology to the existing plant has allowed the cooling temperature to increase by 13 °C while maintaining the same condensing pressure. As a result, significant net increase in electrical efficiency, reduction of auto-consumption and cut down on annual cooling water consumption were obtained.